Peningkatan Daya Saing Produk Melalui Inovasi Produk, Branding dan Sistem Pemasaran Konsinyasi: Increasing Product Competitiveness Through Product Innovation, Branding and Consignment Marketing System - Silaningsih, Endang; Sudarijati, Sudarijati; Kartini, Tini; Hanipah, Imanda; Akhsan, Muhammad; Ningsih, Desi Fitria; Fairuz, Rozaan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Gunung Endut Village in Kalapanunggal, Sukabumi, is known as a place that often produces cassava. Cassava which is rich in carbohydrates and nutrients has become an important basic ingredient for UMKM in this village, especially for the production of cassava chips. Taking action steps carried out by the Community Service (PkM) program team from the Faculty of Economics and Business after seeing the available potential, Team PkM Djuanda University Bogor created a new product called "Stik Si Endut" in the form of innovative frozen cheese cassava sticks. The purpose of this activity is to provide an explanation to UMKM actors regarding the production process of frozen cheese cassava sticks, improving branding, packaging, and distribution strategies through the consignment marketing system. Through preparation and survey stage, counseling, and evaluation methods, this activity is expected to improve skills, product innovation, and the local economy in Gunung Endut Village. This research shows that there is a great opportunity for the diversification of cassava products in the village, with a focus on increasing added value and economic development of the local community.